Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of Bounce What links the Mercedes Formula One team with Google?What links Team S ky and the aviation industry?What connects James Dyson and David Beckh am?They are all Black Box Thinkers.Black Box Thinking is a new approac h to high performance, a means of finding an edge in a complex and fas t-changing world. It is not just about sport, but has powerful implica tions for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on margin al gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prep ared to learn from our mistakes.
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning